Comparison of serum concentrations between different dosing strategies of posaconazole delayed‐release tablet at a large academic medical centre. Issue 4 (1st December 2016) - Welch, Sarah; Pallotta, Andrea; Weber, Catherine; Siebenaller, Caitlin; Cober, Eric; Neuner, Elizabeth
Summary: It is unclear if the prophylaxis dose of 300 mg/day is sufficient for achieving serum concentrations targeting the treatment of invasive fungal infections. To evaluate differences between PCZ serum concentrations in patients receiving the DRT vs the OS and in patients receiving higher doses than 300 mg/day of the DRT, a retrospective review was conducted on inpatients who received PCZ for either treatment or prophylaxis. Baseline demographics including comorbid conditions, indication and dose of therapy were collected. Serum trough concentrations were collected at steady state. Fifty‐seven patients received PCZ during the study period. A total of 35 levels were collected (DRT n = 18, OS n = 17). Patients receiving the DRT had levels >0.7 mcg/mL 100% of the time compared to 58.8% in those receiving the OS. No significant difference was seen in serum concentrations at 300 mg/day (n = 14) vs 400 mg/day (n = 8) of the DRT (1.55 mcg/mL (1.08‐2.50) vs 2.5 mcg/mL (1.85‐2.70), P = .19). The DRT leads to more consistent levels in the therapeutic range than the OS. Standard dosing of 300 mg/day with DRT achieves adequate concentrations for prophylaxis and treatment of IFIs, although further data are needed to determine optimal serum concentrations for treatment.